An Analysis of Student in Writing Recount Text at Ninth Grade Students PKBM Nurul Islam Telagasari - Debby Utami Putri; Yon A. E (Universitas Muhammadiyah Enrekang, 2022)
The purpose of this study was to determine the percentage and to determine the types of errors made by students in writing recount text. Expecially to identify an error students make in using verb in recount text. The method used in this research is qualitative. The qualitative design used in this research is qualitative descriptive. The subjects of this study were 20 students of class 1X PKBM Nurul Islam and all students were taken as samples. Data collection was done by giving tests and interviews with students. The errors were classified into Surface Taxonomi, From the results of this study, it can be seen those verb frequent error made by class X1 PKBM Nurul Islam students with a percentage of 100%. The total omission errors were 19 error or 9,5%, additional errors 5 or 2,5%, 156 misinformation errors or 78% and misordering errors were found 20 or 10%, the total formatting errors were 200 errors or 100%.